Genetics, genomics, grouse, and conservation: use of genetic and genomic data to evaluate conservation actions and characterize populations of Gunnison sage-grouse - Zimmerman, Shawna Jean, author; Aldridge, Cameron L., advisor; Oyler-McCance, Sara J., advisor; Funk, W. Chris, committee member; Hooten, Mevin B., committee member (Colorado State University. Libraries, 2019)
To view the abstract, please see the full text of the document.